Analisis Vegetasi Hutan Dipterocarpaceae campuran di Taman Nasional Kayan Mentarang, Kalimantan Timur - Razali Yusuf (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
A study on plant ecology by using a quadrat  method has been conducted. This study focused on species vegetation richness at some different altitudes. From the sampling area of 2.24 ha, it was identified that there are 1060 trees of 235 species belong to 121 genera of 41 families. Family of  Dipterocarpaceae which was dominated by species of shorea and the most commonest species, especially the upper layer with basal areas reached 25.33 m². Some species adapted well at the location such as Parashorea parvifolia, Shorea ovalis, Shorea johorensis, Garcinia sp, Callophyllum pulcherrimum, Castanopsis philipensis, Lithocarpus blumeanus and Quercus subsericea